Pengaruh Brand Love, Brand Engagement, dan Brand Equity terhadap Repurchase Intention: Studi pada Pengguna Smartphone Samsung di Indonesia - Sita Ningrum Sastri Dewi; Kussudyarsana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Samsung is an electronics brand that is ranked first in 2018 – 2023 as the top brand index category, however, Samsung smartphone products tend to experience a decline from year to year. This shows that the repurchase intention of Samsung smartphone users is not optimal. Therefore, research was used regarding "The Influence of Brand Love, Brand Engagement, and Brand Equity on Repurchase Intention (Study of Samsung Smartphone Users in Indonesia)”. This research was conducted quantitatively descriptively with a sample size of 155 people. The analysis of primary data obtained through surveys involved the utilization of multiple linear regression tests. The research findings indicate that Brand Love, Brand Engagement, and Brand Equity positively influence Repurchase Intention. In addition, there is a strong and meaningful correlation between brand engagement and brand equity in relation to repurchase intention. Furthermore, there is a positive but not statistically significant correlation between the variable of brand love and repurchase intention